Effect of para-net shade level on plant microenvironment, growth, and yield of three strawberry varieties - NUR EDY SUMINARTI; HUSNI THAMRIN SEBAYANG; MOHAMAD DAWAM MAGHFOER; BULAN BULAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Suminarti NE, Sebayang HT, Maghfoer MD, Bulan. 2023. Effect of para-net shade level on plant microenvironment, growth, and yield of three strawberry varieties. Biodiversitas 24: 2149-2155. Plant environmental management through the application of para-net shade and the selection of adaptive varieties for strawberry plants has been carried out from March to June 2020 in Jatikerto.The study used a split-plotdesign by placing shade treatments on the main plot consisting of four types, namely without shade (0%), 25% shading, 50% shading, and 75% shading, while the variety treatment was placed in subplots consisting of three kinds, namely Sweet Charlie, California, and Earlibrite varieties.The 5% F test was used to determine the interaction or significant effect of the treatments, while the 5% HSD test was used to determine differences between treatments.The results showed that there was a significant interaction in observing fruit weight per hectare. In the treatment without shade and with 25% shade, the highest fruit weight was produced by the California variety, 1.06 t ha-1,and 0.80 t ha-1, respectively. Whereas at 50% shade, the highest fruit weight per hectare was found in the Sweet Charlie variety, namely 0.66 t ha-1, and at 75% shade, higher yields were found in the Sweet Charlie and Earlibrite varieties, each of 0.65 t ha-1and 0.55 t ha1. Conclusion: California is a fairly tolerant variety to be developed in the Jatikerto area.